MISTERI PASKAH KRISTUS SEBAGAI PUNCAK SEJARAH KESELAMATAN - Richardo Rengkung; Thomas Lukas Lappy (Pineleng Theological Review, 2026)
The biblical history of salvation originates in humanity’s fall into sin and God’s immediate promise of redemption, articulated in Genesis 3:15 as the protoevangelium. This promise unfolds progressively within Israel’s history through patriarchs, mediators, and prophets, and reaches its definitive fulfillment in Jesus Christ, particularly in the Paschal Mystery of his passion, death, and resurrection. This salvific event constitutes the decisive manifestation of God’s redemptive love, liberating humanity from sin and opening the horizon of eternal life. Catholic theology affirms that, while salvation is fully accomplished in Christ, it is not confined to a past historical moment. Rather, the Paschal Mystery remains efficacious and present throughout history, especially in the Eucharist, where it is sacramentally re-presented. The Church, therefore, is entrusted with the mission to proclaim, celebrate, and embody this mystery until the consummation of time.